Integration of Islamic Values in Educational Management in Optimizing Teacher Competence - Neneng Nurhasanah; Asep Supriatna; Dede Ajeng Arini; Imam Abdullah; Agus, Agus (Bulletin of Science Education, 2025)
Teacher Competence plays a very important role in improving the quality of education, especially in the context of education based on Islamic values. One aspect that can influence teacher competence sis educational management that is integrated with Islamic principles, such as amanah, justice, and responsibility. This study aims to examine the influence of educational management based on Islamic values on improving teacher competence at Integrated Islamic Junior High School (SMPIT) Manbaul Ulum. The method used in this study is a qualitative method with a case study approach. Data were collected through in-depth interviews with the principal, teachers, and administrative staff, as well as direct observation of the implementation of educational management based on Islamic values. The results of the study indicate that educational management based on Islamic values at SMPIT Manbaul Ulum has contributed significantly to improving teacher competence. The Islamic principles applied in every aspect of educational management have succeeded in forming the character of teachers who are more professional and responsible. However, several obstacles were found in the implementation process, such as the limited professional development program based on Islamic values. The implication of this study is the importance of strengthening institutional support and increasing continuous training for teachers. This study contributes to the development of educational management based on Islamic values to improve the quality of education in Islamic schools.